P149/O06 Higher expression of siglec-7/9 on granulocytes and monocytes has a protective role in rheumatoid arthritis. (March 2019) - Andes, F; Zapf, J; Hahn, J; Manger, B; Schett, G; Steffen, U
Abstract : Career situation of first and presenting author: Student for a master or a PhD. Introduction: Prominent features of rheumatoid arthritis (RA) are pain, joint swelling and erosion induced by massive infiltration of immune cells into the inflamed tissue. Among these immune cells, granulocytes and monocytes play a crucial role. Both express sialic acid-binding immunoglobulin-like lectins (Siglecs) −7 and −9 (in mice Siglec-E), trans-membrane proteins generally transmitting inhibitory signals through immunoreceptor tyrosine-based inhibitory motifs in their cytoplasmic tails. So far, there has been only limited research on the effects of Siglecs in RA. Objectives: To evaluate the potential role of Siglec 7- and −9 during disease progression in RA by comparing the expression on blood leukocytes with disease activity in RA patients. Additionally we monitored Siglec-E knockout mice in an experimental arthritis model. Methods: Blood samples from 45 healthy donors (HD) and 37 RA patients were analyzed by flow cytometry for Siglec-7 and −9 expressions on NK cells (CD14+/CD56+/CD3-), granulocytes (CD16+/CD19-) and monocytes (CD14+/CD16-). Expression was correlated with autoantibody positivity and disease severity. Siglec-E knockout mice and wildtype controls were used in a serum transfer induced arthritis model and disease manifestation was monitored by measurement of paw swelling. Additionally we performed functional ex vivo assays to study Siglec impact on granulocytes and monocytes. Results: There was a diminished Siglec-7/9 expression on NK cells from RA patients, especially in highly CCP positive patients (>500 U/ml), while no differences were observed in neutrophils and monocytes compared to healthy controls. Interestingly we observed a correlation between a higher DAS28 score and lower Siglec-9 expression levels on granulocytes in seropositive patients. Siglec-E knockout mice displayed higher disease scores and paw swelling in serum transfer induced arthritis, especially at the peak and the resolution phase. Functional studies unraveled that granulocytes are in a more active state if Siglec-7 and −9 are missing. Conclusions: Together our data support that Siglec-7/9 expression negatively correlates with pathogenesis and disease manifestation in RA patients. We showed in vivo and ex vivo, that Siglecs possess an important role concerning granulocyte and monocyte function and are capable of dampening immune response. Due to their inhibitory potential, Siglecs should be considered as potential therapeutic starting point in future studies. Acknowledgements: This work was supported by DFG (HA 8163/1–1) and STAEDTLER Stiftung (WW/eh20/17). Disclosure of Interest: None declared.